Experimental Adaptation of an RNA Virus Mimics Natural Evolution - Hajimorad, M. R. (American Society for Microbiology (ASM), 2011)
Identification of virulence determinants of viruses is of critical importance in virology. In search of such determinants, virologists traditionally utilize comparative genomics between a virulent and an avirulent virus strain and construct chimeras to map their locations. Subsequent comparison reveals sequence differences, and through analyses of site-directed mutants, key residues are identified. In the absence of a naturally occurring virulent strain, an avirulent strain can be functionally converted to a virulent variant via an experimental evolutionary approach. However, the concern remains whether experimentally evolved virulence determinants mimic those that have evolved naturally. To provide a direct comparison, we exploited a plant RNA virus, soybean mosaic virus (SMV), and its natural host, soybean. Through a serial in vivo passage experiment, the molecularly cloned genome of an avirulent SMV strain was converted to virulent variants on functionally immune soybean genotypes harboring resistance factor(s) from the complex Rsv1 locus. Several of the experimentally evolved virulence determinants were identical to those discovered through a comparative genomic approach with a naturally evolved virulent strain. Thus, our observations validate an experimental evolutionary approach to identify relevant virulence determinants of an RNA virus.